Socioeconomic Status and Childhood Leukemia Incidence in Switzerland - Adam, Martin; Kuehni, Claudia E.; Spoerri, Adrian; Schmidlin, Kurt; Gumy-Pause, Fabienne; Brazzola, Pierluigi; Probst-Hensch, Nicole; Zwahlen, Marcel (Frontiers in Oncology, 2015)
Socioeconomic status (SES) discrepancies exist for child and adult cancer morbidity and are a major public health concern. In this Swiss population-based matched case-control study on the etiology of childhood leukemia, we selected the cases from the Swiss Childhood Cancer Registry (SCCR) diagnosed since 1991 and the controls randomly from census. We assigned eight controls per case from the 1990 and 2000 census and matched them by year of birth and gender. SES information for both cases and controls was obtained from census records by probabilistic record linkage. We investigated the association of SES with childhood leukemia in Switzerland, and explored whether it varied with different definitions of socioeconomic status (parental education, living condition, area-based SES), time period and age. In conditional logistic regression analyses of 565 leukemia cases and 4433 controls, we found no consistent evidence for an association between SES and childhood leukemia. The odds ratio comparing the highest with the lowest SES category ranged from 0.95 (95% CI: 0.71-1.26; ptrend=0.73) for paternal education to 1.37 (1.00-1.89; ptrend=0.064) for maternal education. No effect modification was found for time period and age at diagnosis. Based on this population-based study, which avoided participation and reporting bias, we assume the potential association of socioeconomic status and childhood leukemia if existing to be small. The study results imply that future etiological investigations on leukemia incidence in Western Europe should not focus on socioeconomic status as individual risk factor or strong confounder in research on other risk factors for childhood leukemia.